Age-dependent changes in microscale stiffness and mechanoresponses of cells - Zahn, Jasmin T.; Louban, Ilia; Jungbauer, Simon; Bissinger, Martin; Kaufmann, Dieter; Kemkemer, Ralf; Spatz, Joachim P. (Small, 2011)
Cellular ageing can lead to altered cell mechanical properties and is known to affect many fundamental physiological cell functions. To reveal age-dependent changes in cell mechanical properties and in active mechanoresponses, the stiffness of human fibroblasts from differently aged donors was determined, as well as the cell’s reaction to periodic mechanical deformation of the culture substrate, and the two parameters were correlated. A comparison of the average Young’s moduli revealed that cells from young donors (<25 years) are considerably stiffer than cells from older donors (>30 years). The reduced stiffness of cells from the older donor group corresponds to the measured decrease of actin in these cells. Remarkably, cells from the older donor group show a significantly faster reorganization response to periodic uniaxial tensile strain than cells from the young donor group. The impact of a reduced amount of actin on cell stiffness and cell reorganization kinetics is further confirmed by experiments where the amount of cellular actin in cells from the young donor group was decreased by transient siRNA knockdown of the actin gene. These cells show a reduced stiffness and enhanced reorganization speed, and in this way mimic the properties and behavior of cells from the older donor group. These results demonstrate that mechanical properties of human fibroblasts depend on the donor’s age, which in turn may affect the cells’ active responses to mechanical stimulations.
Gesehen am 19.12.2022